EFFECTIVENESS OF PLATELET TRANSFUSION IN DENGUE PATIENTS IN A TERTIARY CARE HOSPITAL - V., VIJAY ANAND; SHARMA, ANKIT (International Journal of Current Pharmaceutical Research, 2023)
Objective: Dengue has been emerging as rapidly spreading and dreaded mosquito-borne disease caused by the bite of Aedes Aegypti Mosquito. Clinical features are variable and presents with Dengue fever or Dengue Hemorrhagic fever or more severe Dengue shock syndrome. Thrombocytopenia is presenting feature in all Dengue cases and some often presents with bleeding. Platelet transfusions are given in patients with haemorrhagic symptoms. While medical fraternity globally recognizes the role of platelet transfusion in the management of hospitalized dengue patients the exact indications and situations in which these are to be transfused may vary. Since there is inherent risk associated with the transfusion of blood/blood-component, it is imperative for each institution (or country) to lay their own criteria for transfusion of these blood components. The present study was conducted to lay precise criteria and transfusion trigger for platelet transfusion in our setup. Methods: The present study was conducted on 225 serologically confirmed dengue patients admitted at sawaimansign Hospitals between 1" of August to 30th of November 2022. Clinical data, reports of hematological investigation, platelets requirements and data obtained from SHealth services. Results: In the serologically confirmed cases, the prevalence of thrombocytopenia (count less than 100,000/cumm) was 84.88% on admission and bleeding was recorded in 22 (9.7%) patients. About 96 (42.6%) patients of dengue cases received platelet transfusion. Among them 47 (20.88%) patients had a platelet count<20,000/cumm, 43 (19.11%) had a platelet count in the range of 21-40.000/cumm, while 6 (2.66%) patients had the platelet count in between 41 and 50.000/cumm. Out of 49 patients with a platelet count>20,000/cumm, 18 patients had hemorrhagic manifestations such as petechiae, gum-bleeding, epistaxis, etc., which necessitates the use of platelet transfusion. However, 31 patients received inappropriate platelet transfusion. Conclusion: This study suggests that bleeding occurs more often in patients with severe thrombocytopenia. High-risk patients having platelet count<20,000/cumm and risk of bleeding require urgent platelet transfusion. Patients with a platelet count 21-40,000/cumm are in moderate risk and require platelet transfusion only if they have any haemorrhagic manifestations and other superadded conditions.